Combining ART and FBP for improved fidelity of tomographic BOS. (25th July 2016) - Hartmann, Ulrich; Seume, Joerg R
Abstract: Engine component defects along the hot-gas path (HGP) of jet engines influence the density distribution of the flow, and thus result in characteristic patterns in the exhaust jet. These characteristic patterns can be reconstructed with the optical background-oriented schlieren (BOS) method in a tomographic set-up, which in turn allows the identification of defects inside the engine through an exhaust jet analysis. The quality of the tomographic reconstruction strongly influences how easily defects can be detected inside the jet engine. In particular, the presence of high gradients in the reconstruction area has a strong impact on the reconstruction quality. An algebraic reconstruction algorithm (ART) is implemented and compared to a filtered-back projection (FBP) algorithm in terms of the capability of performing high-gradient tomographic BOS reconstructions. A combination of both algorithms is presented which significantly improves the reconstruction quality of high-gradient tomographic BOS in terms of artifact reduction. The combination of both algorithms is applied to both synthetic and real measurement data in this paper, in order to show possible applications and the achievable improvement of high-gradient tomographic BOS reconstructions.